Intercomparison of Atmospheric Carbonyl Sulfide (TransCom‐COS; Part One): Evaluating the Impact of Transport and Emissions on Tropospheric Variability Using Ground‐Based and Aircraft Data. Issue 6 (13th March 2023) - Remaud, Marine; Ma, Jin; Krol, Maarten; Abadie, Camille; Cartwright, Michael P.; Patra, Prabir; Niwa, Yosuke; Rodenbeck, Christian; Belviso, Sauveur; Kooijmans, Linda; Lennartz, Sinikka; Maignan, Fabienne; et al.
Abstract: We present a comparison of atmospheric transport model (ATM) simulations for carbonyl sulfide (COS), within the framework of the atmospheric tracer transport model intercomparison project "TransCom‐COS." Seven ATMs participated in the experiment and provided simulations of COS mixing ratios over the years 2010–2018, using state‐of‐the‐art surface fluxes for various components of the COS budget: biospheric sink, oceanic source, sources from fire and industry. The main goal of TransCom‐COS is to investigate the impact of the transport uncertainty and emission distribution in simulating the spatio‐temporal variability of tropospheric COS mixing ratios. A control case with seasonal surface fluxes of COS was constructed. The results indicate that the COS mixing ratios are underestimated by at least 50 parts per trillion (ppt) in the tropics, pointing to a missing tropical source. In summer, the mixing ratios are overestimated by at least 50 ppt above 40°N, pointing to a likely missing sink in the high northern latitudes. Regarding the latitudinal profile, the model spread is greater than 60 ppt above 40°N in boreal summer. Regarding the seasonal amplitude, the model spread reaches 50 ppt at 6 out of 15 sites, compared to an observed seasonal amplitude of 100 ppt. All models simulated a too late minimum by at least 2–3 months at two high northern‐latitude sites, likely owing to errors in the seasonal cycle in the ocean emissions. This study highlighted the shortcomings in the COS global budget that need to be resolved before using COS as a photosynthesis tracer. Plain Language Summary: In this study, we evaluate the state‐of‐the‐art fluxes for various components of the carbonyl sulfide (COS) budget: biospheric sink, oceanic source, sources from fire and industry. A control case with seasonal surface fluxes of COS was constructed. Seven atmospheric transport models provided simulations of COS mixing ratios. Then, the simulated mixing ratios were evaluated against atmospheric measurements at several surface sites. Results show that all models fail to capture the observed latitudinal distribution and that the model spread is small compared to the model‐observation mismatch. In summer, the overestimated mixing ratios above 40°N point to a likely missing sink in the high northern latitudes. The underestimated mixing ratios in the tropics point to a missing tropical source. This study highlighted the shortcomings in the COS global budget that need to be resolved before using COS as a photosynthesis tracer. Key Points: The model‐observation mismatch suggests there is a missing source in the tropics and a missing sink in the high northern latitude in summer At northern latitude sites, the model spread in seasonal amplitude reaches 50 ppt compared to a mean seasonal amplitude of about 100 ppt The diurnal rectifier effect is small, decreasing the seasonal amplitude by up to 20% at continental sites